Penerapan Konsep Tri Hta Karana Di Daya Tarik Wisata Danau Beratan - Yanuarius F Lagut; Ida Bagus Suryawan (Program Studi Sarjana Pariwisata, Fakultas Pariwisata, Universitas Udayana, 2017)
The Development of the Tri Hita Karana concept start begins the study results by Pusat Kajian Bali in 2000. This study involved the local communities, scientists and various observers of development. This study resulted in a lot of concepts about the development of Tri Hita Karana which require development in Bali based on the concept. Tri Hita Karana concept is the basic for the implementation or benchmarks in sustainable tourism development in Bali. Beratan Lake is one of the many examples of tourist attraction that based on the concept of Tri Hita Karana. Researchers used the Tri Hita Karana Award and Accreditation in 2014 as a reference to provide an assessment of the existence of the Beratan Lake. The results of this study showed that the condition of the Beratan Lake at the stage of development belonging to very good.